Blood Metabolites of Murrah Buffalo Heifer on Supplementation of Different Sources of Rumen Bypass Proteins - Kumari, A.; Gulati, H. K.; Kumar, S.; Sihag, S.; Kumar, M. (Indian Journal of Animal Nutrition, 2022)
Eighteen Murrah buffalo heifers, at BRC, LUVAS, Hissar distributed into three treatments to evaluate the effect of supplementation of different sources of bypass proteins on blood biochemical profile. Heifers in all three group fed similar basal diets, in treatment T2 10% of crude protein requirement was replaced with commercially available soya bypass protein and in treatment T3 10% of crude protein requirement was replaced with natural bypass protein i.e fish meal. Blood samples were collected with or without anti-coagulant for biochemical and serum mineral analysis respectively, at the start of experiment and thereafter at monthly intervals for a period of 120 days. Feeding of bypass protein result in significant increase (P<0.05) in concentration of plasma glucose, total protein, globulin, and calcium but concentration of other biochemical parameters, serum mineral values and activity of enzymes showed no significant difference among the treatments.